A Persepsi Nelayan Terhadap Kegiatan Penyuluhan Perikanan Desa Muara Muntai Ulu Kecamatan Muara Muntai Kabupaten Kutai Kartanegara: Persepsi Nelayan Terhadap Kegiatan Penyuluhan - Muhammad Rizky; Eko Sugiharto; Gusti Haqiqiansyah (2339-1324, 2023)
Extension activities in an effort to develop fishing are held to improve the performance of fishermen in Muara Muntai Ulu Village. With the extension, it can help fishermen in increasing productivity, business efficiency, business income, improving the quality of life as well as increasing awareness in preserving environmental functions. Fisheries extension activities cause various perceptions from various fishermen in Muara Muntai Ulu. This study aims to determine the level of perception of fishermen on fishery extension activities in Muara Muntai Ulu Village, Muara Muntai District, Kutai Kartanegara Regency. This study uses the Total Sampling method. Data analysis used descriptive qualitative Likert scale. According to the results of the Likert scale analysis of all indicators, the average Fisheries Extension activity is in the medium category. In the Fishermen's Perception research on Extension activities partially, all indicators are in the medium and high categories. Indicators that get a moderate score are facilitating the learning process of key players and business actors, Ensuring easy access of fishermen to sources of information, technology, and other resources, assisting fishermen in developing their capabilities so that they are highly competitive, productive, good sustainable business governance and Help analyze and solve fishermen's problems. While the indicators that get high scores are improving leadership, managerial and entrepreneurial abilities.